The permanent rebellion: An interpretation of Mapuche uprisings under Chilean colonialism. (1st June 2021) - Pairican, Fernando; Urrutia, Marie Juliette
Abstract : This article approaches the rebellions of the Mapuche people from a longue-durée perspective, from the Occupation of the Araucanía in 1861 to the recent events of 2020. Among other things, the article explores the Popular Unity (UP) period, and the 'Cautinazo' in particular, considered here as an uprising that synthesised the discourses and aspirations of the Mapuche people dating back to the Occupation, while also repoliticising them by foregrounding demands for land restitution. This experience created the conditions for a new cycle of mobilisation that began in the twenty-first century. In other words, the Agrarian Reform of the UP era set the stage for more recent rebellions that are once again challenging colonial problems related to private property rights, the usurpation of land and agricultural aggression. In seeking responses to these problems, the Mapuche movement of the early twenty-first century is being revitalised.